Development and Molecular Cytogenetic Identification of a New Wheat–Psathyrostachys huashanica Keng Translocation Line Resistant to Powdery Mildew - Liu, Yuxiu; Huang, Shuhua; Han, Jing; Hou, Chenchen; Zheng, Dasheng; Zhang, Zhengmao; Wu, Jun (Frontiers in Plant Science, 2021)
Psathyrostachys huashanica Keng, a wild relative of common wheat with many desirable traits, is an invaluable source of genetic material for wheat improvement. Few wheat–P. huashanica translocation lines resistant to powdery mildew have been reported. In this study, a wheat–P. huashanica line, E24-3-1-6-2-1, was generated via distant hybridization, ethyl methanesulfonate (EMS) mutagenesis, and backcross breeding. A chromosome karyotype of 2n = 44 was observed at the mitotic stage in E24-3-1-6-2-1. Genomic in situ hybridization (GISH) analysis revealed four translocated chromosomes in E24-3-1-6-2-1, and P. huashanica chromosome-specific marker analysis showed that the alien chromosome fragment was from the P. huashanica 4Ns chromosome. Moreover, fluorescence in situ hybridization (FISH) analysis demonstrated that reciprocal translocation had occurred between the P. huashanica 4Ns chromosome and the wheat 3D chromosome; thus, E24-3-1-6-2-1 carried two translocations: T3DS·3DL-4NsL and T3DL-4NsS. Translocation also occurred between wheat chromosomes 2A and 4A. At the adult stage, E24-3-1-6-2-1 was highly resistant to powdery-mildew-causing lethal pathotypes that are prevalent in China. Further, the spike length, numbers of fertile spikelets, kernels per spike, thousand-kernel weight, and grain yield of E24-3-1-6-2-1 were significantly higher than those of its wheat parent 7182 and addition line 24-6-3-1. Thus, this translocation line, which is highly resistant to powdery mildew and has excellent agronomic traits, could be used as a novel promising germplasm for breeding resistant and high-yielding cultivars.